Mechanically interlocked stretchable nanofibers for multifunctional wearable triboelectric nanogenerator. (December 2020) - Li, Yi; Xiong, Jiaqing; Lv, Jian; Chen, Jian; Gao, Dace; Zhang, Xiaoxing; Lee, Pooi See
Abstract: Nanofibers with good softness and high surface specific area are excellent choices for wearable triboelectric nanogenerator (TENG), despite that the deformability and durability remain challenging in seamless integration with daily textiles/clothes. Herein, we propose a physical interlocking strategy to realize a self-interlocked stretchable, breathable and waterproof nanofibers-membrane by simultaneous electrospinning of poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) and electrospraying of styrene-ethylene-butylene-styrene (SEBS). The electrosprayed SEBS microspheres serve as the elastic binders and hydrophobic modifiers for enhancing stretchability and waterproofness of the electrospun PVDF-HFP fibers network. By means of a printable electrode consisted of liquid metal (gallium indium tin particles) and silver flakes, a stretchable nanofibers-based TENG (SNF-TENG) with high triboelectric output (85 V, 219.66 mW m −2 ) and electrical durability was demonstrated, capable of harvesting energy from human motions and flowing water, powering 200 commercial LEDs and an electronic watch. The stretchable nanofibers membrane shows favorable mechanical compliance, which can be facilely integrated onto stretchable textile to fabricate textile-TENG, promising for comfortable wearable applications for power sources, smart raincoat, self-powered e-skin and tactile interactive interfaces. Graphical abstract: Image 1 Highlights: ● Self-interlocked stretchable, hydrophobic and breathable nanofibers are realized by simultaneous electrospin-electrospray strategy. ● Stretchable nanofibers integrated with printable liquid metal elastic conductor enabled facile preparation of a stretchable textile TENG. ● Textile-TENG with great stretchability (125%), high durability and great mechanical transformability are fabricated. ● Stretchable nanofiber based wearable TENG demonstrates exceptional energy harvesting and tactile interactive sensing capabilities.